2013
DOI: 10.1002/jctb.4242
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reaction network of Pichia pastoris with glycosylation reactions: Flux analysis for erythropoietin production

Abstract: BACKGROUND Biochemical reaction network of Pichia pastoris was improved by including N‐ glycosylation pathway reactions to determine the intracellular reaction rates for glycosylated protein production. RESULTS When co‐substrate sorbitol was replaced with mannitol, 12‐fold increase in erythropoietin flux was obtained as a result of 1.2‐ and 2.4‐fold increase in glucose‐6‐phosphate (G6P) formation from fructose‐6‐phosphate (F6P) and 3‐phospho‐D‐glycerate (3PG) formation from glyceraldehyde‐3‐phosphate (G3P), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(61 reference statements)
0
3
1
Order By: Relevance
“…A). This is in contrast to previous computational modelling that was performed of N‐glycosylation in P. pastoris (Eskitoros et al, ), where it was concluded that yields of humanized N‐glycosylated proteins are higher than of native N‐glycosylated proteins. The reduced theoretical yield of humanized in comparison to native N‐glycosylation can be explained by the size of the N‐glycan complex, which contains 70 and 84 carbons in native and humanized forms respectively.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…A). This is in contrast to previous computational modelling that was performed of N‐glycosylation in P. pastoris (Eskitoros et al, ), where it was concluded that yields of humanized N‐glycosylated proteins are higher than of native N‐glycosylated proteins. The reduced theoretical yield of humanized in comparison to native N‐glycosylation can be explained by the size of the N‐glycan complex, which contains 70 and 84 carbons in native and humanized forms respectively.…”
Section: Resultscontrasting
confidence: 99%
“…In comparison with other models of N‐glycosylation in P. pastoris (Barrigon et al, ; Eskitoros et al, ), our model is in the context of the whole of P. pastoris metabolism, allows both native and humanized N‐glycosylation of multiple recombinant proteins and estimates N‐glycosylation of the native proteome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations